Manajemen Jaringan menggunakan Remote Authentication Dial in User Service (RADIUS) - Abdul Majid (Universitas Pancasakti, 2021)
Networking today is a much needed service. Existing problems include user authentication, hotspot user management, bandwidth management and any unwanted intruders. It is necessary to the development of a network system that can provide security for user authentication and bandwidth management. Network development means developing new systems and will replace the old system or improve the existing system. Particularly the issue of authentication and bandwidth. Type of this research is the Applied Research with the system development using the NDLC (Network Development Life Cycle) method. Data collection method using interviews, observation and literature study. The Method system testing is adopts the ISO 9126 standards such as functionality, reliability, usability and efficiency. This research resulted in the network security system to have a good quality with a percentage of 82.5% and meet the needs of organizations in Pondok Pesantren Madinatunnajah.